Determinants of Non-Performing Loans in Indonesian Public Banks: A Case Study of Covid-19 Pandemic - Ezha Lintang Erdiningrum; Satria, Dias (Contemporary Studies in Economic, Finance and Banking, 2025)
Banks as intermediary institutions play an important role in a country's econo-my. When operating, there are several risks that must be faced and managed by banks. One of them is credit risk which is measured using the NPL ratio as the main indicator. Although there have been many studies on the determinants of NPL, there is still a re-search gap related to the impact of the global crisis such as the COVID-19 pandemic. So the purpose of this study is to identify the determinants of NPL in public banks in Indone-sia or banks that have been listed on the IDX during the period Q1 201 to Q4 2023. The results of the study using a dynamic panel data model with the System GMM approach show that inflation and solvency ratios have a negative and significant effect on NPL while interest rates, BOPO and Dummy COVID-19 have a positive effect on NPL. While GDP, ROE, SIZE and LLP have no effect on NPL. The results of this study can be a con-sideration for policy makers in formulating policies related to NPL and can provide in-sight for banks in managing credit risk or optimizing risk management strategies amidst economic dynamics.